2016
DOI: 10.1007/s10854-016-5163-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of number of SILAR cycles on morphological, optical and photo catalytic properties of cadmium sulfide–titania films

Abstract: In this paper, cadmium sulfide-titania nanocomposites were successfully synthesized by electrochemical anodizing and successive ionic layer adsorption and reaction (SILAR) methods. Cadmium sulfide was successfully deposited on titania nanotubes with tunable loading amounts by controlling deposition cycles of SILAR. The morphology, crystal structure, elemental composition and light absorption capability of samples were characterized by FE-SEM, XRD, EDX and UV-Vis methods. Titania nanotubes with 90-220 nm in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In recent years, much effort has been devoted to encapsulate nanoparticles (NPs) of metals, metal oxides, metal oxide composites, organic polymers, , polyoxometalates, , and MOFs , into MOFs to form hybrid core–shell composites/structures. These hybrid core–shell materials possess not only the intrinsic properties of the NPs and MOFs but also synergistic properties that explore their more new applications (Table ) in various fields, such as selective photocatalysis/catalysis, ,,,,, therapy, , and gas storage and sensing , and as supercapacitors and carriers for electrode materials. , NPs@MOFs core–shell composites have been prepared either by using MOFs as templates to generate and embed nanoparticles within their cavities or by encapsulating presynthesized nanoparticles stabilized with certain surfactants, capping agents, or even ions, ,,, and usually it has been observed that nanoparticles do not occupy the MOF cavities (because their hydrodynamic radius is much larger than the size of cavity of MOFs), but instead are surrounded by grown MOF particles.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, much effort has been devoted to encapsulate nanoparticles (NPs) of metals, metal oxides, metal oxide composites, organic polymers, , polyoxometalates, , and MOFs , into MOFs to form hybrid core–shell composites/structures. These hybrid core–shell materials possess not only the intrinsic properties of the NPs and MOFs but also synergistic properties that explore their more new applications (Table ) in various fields, such as selective photocatalysis/catalysis, ,,,,, therapy, , and gas storage and sensing , and as supercapacitors and carriers for electrode materials. , NPs@MOFs core–shell composites have been prepared either by using MOFs as templates to generate and embed nanoparticles within their cavities or by encapsulating presynthesized nanoparticles stabilized with certain surfactants, capping agents, or even ions, ,,, and usually it has been observed that nanoparticles do not occupy the MOF cavities (because their hydrodynamic radius is much larger than the size of cavity of MOFs), but instead are surrounded by grown MOF particles.…”
Section: Introductionmentioning
confidence: 99%
“…Distilled water was used to prepare all the aqueous solutions. TiO 2 nanotubes were prepared by anodisation of titanium sheets in ethylene glycol electrolyte containing NH 4 F and water at 60 V for 6 h in a two-electrode configuration using a graphite plate as the cathode electrode [22]. TiO 2 nanotube/Ti samples were then rinsed with distilled water and air dried.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the plate was immersed in a solution of S 2− for 5 minutes and rinsed with water to remove excess S 2− , thereby completing a single SILAR deposition cycle. This process was repeated for six cycles based on the study of the optimal conditions for the synthesis of CdS/TiO2 nanocomposites [24]. By varying the concentration of the precursors using composite values of 0 M, 0.05 M, 0.1 M, and 0.2 M, composite samples with different CdS contents were obtained and denoted as T, CT 0.05, CT 0.1, and CT 0.2, respectively.…”
Section: Preparation Of Tntas and Synthesis Of Cds/tntasmentioning
confidence: 99%